PISA Test 2018 and Issues Related Teaching Reading Informational Texts in Vietnam's Junior High School - Hien, Pham Thi Thu; Huong, Nguyen Thu (VNU Journal of Science: Education Research, 2022)
Information text were first put into official teaching according to the provisions of the Philology Curriculum 2018. From the school year 2021-2022, junior high school students in grade 6 begins to learn reading and writing this type of text. In order to facilitate the teaching and assessment of information literacy reading comprehension in secondary schools effectively, the article introduces and analyzes the PISA test in 2018 in the field of reading informational texts, thereby offering a number of solutions to improve the effectiveness of teaching reading comprehension of this type of text in Vietnamese junior high schools.